(untitled) (Revista de Ciências Agroveterinárias, 2002)
Tetanus is a highly fatal infectious disease of all species of domestic animals and man, caused by the toxin of Clostridium tetani. It is described a case of tetanus in a puppie with generalized muscle stiffness following caudectomy. The spasm, recent history of caudectomy, and no lesions at necropsy and histologycal studies confirmed the diagnosis.